Shirokinsky ore cluster (eastern Transmbaikal): formation conditions, petrochemistry of rocks and ores, association between mineralization and magmatism - Bair Namzhilovich Abramov; Yuri Aleksandrovich Kalinin; Konstantin Romanovich Kovalev; Victor Fedorovich Posokhov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2017)
Relevance of the work is in revealing conditions of formation of rocks and ores from the Shirokinsky ore cluster. The distinctive feature of the ore cluster is the high gold mineralization of its polymetallic ores. The concentrations of gold in ores and its reserves correspond to typical lode gold deposits. The targets of investigation are the Novo-Shirokinsky gold-polymetallic deposit that is the largest with respect to reserves and massively smaller - the Lugiinsky gold-polymetallic and Kochkovsky gold-antimony deposits. The aim of the research is to identify petrochemical features of rocks and ores; to reveal mineralization sources of Shirokinsky ore cluster. Methods of investigation. X-ray fluorescence analysis was used (at GIN S RAS, Ulan-Ude) for determining an element composition of rocks. Content of major elements was determined by the standard chemical method, concentrations of rare earth elements were determined using sorption-atomic-emission spectrometer with inductively coupled plasma (ISP-SAES) (at GIN SB RAS, Ulan-Ude). Determination of oxygen isotopic composition was performed using the MIR 10-30 equipment (at Common User Center, Irkutsk). The authors investigated sulfide sulfur isotopic composition and contents of Au and Ag at CUC SB RAS of multi-element and isotope investigation (Novosibirsk). Investigation results. It was ascertained that deposits of the Shirokinsky ore cluster are derivatives of Taininsky volcanic-dome structure formation. Its magmatic rocks serve as sources of ore matter. This is supported by zonal distribution of ore mineralization around the magmatic center, as well as by the data on isotope compositions of oxygen and carbon of ore-bearing veins and sulfur of sulfide ore minerals indicating their magmatic source. The geochemical features of intrusive and volcanic igneous rocks of the Shirokinsky ore cluster evidence the presence of mantle constituent and adakites. Formation of lead-zink ores is associated with differentiated, different depth magmatic magma chambers. This is proved by the peculiarities of REE distribution in ores.